PADI2‐Catalyzed MEK1 Citrullination Activates ERK1/2 and Promotes IGF2BP1‐Mediated SOX2 mRNA Stability in Endometrial Cancer. Issue 6 (29th January 2021) - Xue, Teng; Liu, Xiaoqiu; Zhang, Mei; E, Qiukai; Liu, Shuting; Zou, Maosheng; Li, Ying; Ma, Zhinan; Han, Yun; Thompson, Paul; Zhang, Xuesen
Abstract: Peptidylarginine deiminase II (PADI2) converts positively charged arginine residues to neutrally charged citrulline, and this activity has been associated with the onset and progression of multiple cancers. However, a role for PADI2 in endometrial cancer (EC) has not been previously explored. This study demonstrates that PADI2 is positively associated with EC proregression. Mechanistically, PADI2 interacting and catalyzing MEK1 citrullination at arginine 113/189 facilitates MEK1 on extracellular signal‐regulated protein kinases 1/2 (ERK1/2) phosphorylation, which activates insulin‐like growth factor‐II binding protein 1 (IGF2BP1) expression. Furthermore, RNA immunoprecipitation (RIP) and RNA stability analyses reveal that IGF2BP1 binds to the m 6 A sites in SOX2 ‐3′UTR to prevent SOX2 mRNA degradation. Dysregulation of IGF2BP1 by PADI2/MEK1/ERK signaling results in abnormal accumulation of oncogenic SOX2 expression, therefore supporting the malignant state of EC. Finally, PADI2 gene silencing, inhibiting MEK1 citrullination by PADI2 inhibitor, or mutation of MEK1 R113/189 equally inhibits EC progression. These data demonstrate that PADI2‐catalyzed MEK1 R113/189 citrullination is a critical diver for EC malignancies and suggest that targeting PADI2/MEK1 can be a potential therapeutic approach in patients with EC. Abstract : Peptidylarginine deiminase II (PADI2) is highly expressed in endometrial cancer (EC) and promotes its progression. Mechanistically, PADI2‐catalyzed MEK1 citrullination at arginine 113 and 189 promotes MEK1 on ERK1/2 phosphorylation, leading to an increase of insulin‐like growth factor‐II binding protein 1 (IGF2BP1) expression. Aberrant activation of IGF2BP1 stabilizes oncogenic Sox2 mRNA, therefore supporting the malignant state of EC.